2016
DOI: 10.1590/0103-6440201302449
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Three Single Instrument Systems in the Preparation of Long Oval Canals

Abstract: This study aimed to evaluate the performance of the Wave One, Easy ProDesign Logic and One Shape systems in the preparation of long oval root canals. Forty-two mandibular incisors were randomized into three groups: Group I, Wave One Primary (WO) (#25.08); Group II, Easy ProDesign Logic (EPL) (#25.06) and Group III, One Shape (OS) (#25.06). Micro-computed tomography scans were obtained pre- and post-preparation of the samples. Instrument fractures or loss of working length did not occur in any of the groups. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
14

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 29 publications
0
30
0
14
Order By: Relevance
“…However, in spite of the increase in volumetric values, a higher percentage of untouched areas were also observed for this system. In previous studies, WaveOne, for example, promoted a higher increase in the volume value of the canal, with a similar percentage of uninstrumented surfaces of oval canals to Easy ProDesign Logic and OneShape systems [27]. It was also observed that although the SAF system touched the canal walls to a larger extent, it removed less dentin in the preparation of oval root canals [18].…”
Section: Discussionmentioning
confidence: 74%
“…However, in spite of the increase in volumetric values, a higher percentage of untouched areas were also observed for this system. In previous studies, WaveOne, for example, promoted a higher increase in the volume value of the canal, with a similar percentage of uninstrumented surfaces of oval canals to Easy ProDesign Logic and OneShape systems [27]. It was also observed that although the SAF system touched the canal walls to a larger extent, it removed less dentin in the preparation of oval root canals [18].…”
Section: Discussionmentioning
confidence: 74%
“…1,2,3,4,5 Since 2012, new protocols for biomechanical root canal preparation have been developed using nickeltitanium (NiTi) instruments, whose flexibility and resistance to torsion allow their use in a continuous rotating movement; these in turn reduce the working time, operator fatigue, and the risk of operative accidents. 6,7,8,9,10,11,12,13,14,15 NiTi instruments have been developed with various geometric conformations, 8 with the most significant design difference being the taper with conicity ranging from 2% to 12%, compared to the standard 2% taper of stainless steel instruments established by ANSI/ADA in 1976 and updated in 1982. 8 NiTi rotary instruments were first commercialized in the 1990s, and since then about 700 studies have been published in journals indexed in PubMed before June 2010.…”
Section: Introductionmentioning
confidence: 99%
“…These instruments are manufactured with a M-Wire alloy from a thermal treating process of the NiTi alloy, which provides greater flexibility and resistance to cyclic fatigue than the conventional NiTi alloy. 4,9,11,13,15,33,34,35,36,37,38,39,40,41,42,43,44,45 The movement dynamics of these instruments, known as reciprocating, is the rotation in the counterclockwise direction (cutting direction) followed by a less extensive clockwise rotation (instrument releasing direction), facilitating continuous and progressive movement toward apical. 15,26 According to some authors, the reciprocating movement reduces the risk of torsion fracture because the instrument is not subjected to the stress levels caused by a continuous rotary motion.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations